Let's complete the process step by step:
-
Start with the equation: \[ -2(15r - 12) = -17r + 11 \]
-
Apply the distributive property: \[ -2 \cdot 15r + -2 \cdot -12 = -17r + 11 \] This simplifies to: \[ -30r + 24 = -17r + 11 \]
-
Now, add \( 17r \) to both sides: \[ -30r + 17r + 24 = 11 \] This simplifies to: \[ -13r + 24 = 11 \]
-
Subtract 24 from both sides: \[ -13r = 11 - 24 \] This simplifies to: \[ -13r = -13 \]
-
Finally, divide both sides by \(-13\): \[ r = \frac{-13}{-13} \] This simplifies to: \[ r = 1 \]
So the missing terms are:
- On the line for \( -30r + \): 24
- On the line for \( r = \): 1
- The final line for "Divide both sides by": –13